Food Preference and Food Consumption of Primary Grade Students - Glendoris G. Galia; Ellen Mae Morano; John Mar M. Cuayzon; Josephine B. Buendia; Clarisa C. Somono; Leah D. Gravillo; Alma Sonia Sanchez-Danday; Ariel G. Salarda (East Asian Journal of Multidisciplinary Research, 2023)
This study investigated the food preferences and consumption of elementary school pupils and the factors that influence them. A stratified random sampling with equal allocation was used to determine the respondents of the study from among the pupils in an elementary school in Palo, Leyte. The 3-point hedonic food preference scale and the 3-point hedonic food consumption scale were also used in the study to determine which foods were preferred and consumed by the pupils. The scale used in this study was based on the foods available in the respondent’s environment and the factors reported in the relevant research literature. The gathered data were subjected to different statistical treatments in order to answer the research questions. This study was able to determine the food preferences and food consumption of basic education students. Moreover, the study findings may provide deeper insights into food preference and food consumption among elementary school pupils and contribute useful information to future research.